Pengaruh Harga, Promosi Penjualan dan Citra Merek Nike terhadap Minat Pelanggan Produk Nike: Studi Kasus Mahasiswa Fakultas Ekonomi dan Bisnis Islam UIN Sumatera Utara - Al farizi Kurniawan; Imsar Imsar; Nurbaiti Nurbaiti (LP3M INSTITUT KH YAZID KARIMULLAH, 2026)
The purpose of this study is to determine the Effect of Price, Sales Promotion and Nike Brand Image on Customer Interest in Nike Products (Case Study of FEBIUINSU Students). This research method is quantitative with the population used in this study are all FEBIUINSU students. The sample is 98 people. The type and source of data that will be used in this study is primary data. The questionnaire distributed is in the form of a google form that can be directly filled out by respondents. In this study, validity testing and reliability testing used the Cronbach Alpha coefficient technique (á) with the help of SPSS 21.0 for Windows. The results of this study show 1. The results of this study indicate that the Price Variable shows a calculated t value greater than the t table (3.421> 1.842), or sig <α (0.001 <0.005). meaning that the Price variable has a positive and significant effect on Customer Interest, thus the first hypothesis is accepted. Price is related to how consumers understand price information as a whole and gives it a deep meaning to them. Price is often the target of research rather than objective price because when they buy something, consumers usually do not think about the price of the product accurately; however, based on their internal, they consider the price of the product as cheap, reasonable, or expensive. 2. The results of this study indicate that, the Sales Promotion Variable shows a calculated t value greater than the t table (5.921 > 1.842), or sig <α (0.000 < 0.005). means that the Sales Promotion variable has a positive and significant effect on the decision of Customer Interest, thus the second hypothesis is accepted. 3. The results of this study indicate that the Brand Image Variable shows a calculated t value greater than the t table (3.521 > 1.842), or sig <α (0.003 < 0.005). means that the Brand Image variable has a positive and significant effect on Customer Interest, thus the third hypothesis is accepted. The variables of price, sales promotion, brand image together have a positive effect simultaneously on customer interest. And this also concludes that the fourth hypothesis is accepted. Sales promotion, brand image together have a simultaneous positive effect on customer interest. And this also concludes that the fourth hypothesis is accepted.